Financial Ratios and Perceived Household Financial Satisfaction - Scott Garrett; Russell N James III (Journal of Financial Therapy, 2013)
This paper tests the relative strength of three objective measures of financial health (using the solvency, liquidity, and investment asset ratio) in predicting a household’s subjective feeling of current financial satisfaction. Using a sample of 6,923 respondents in the 2008 Health and Retirement Study this paper presents evidence of two main findings: 1) the solvency ratio is most strongly associated with financial satisfaction levels based on a cross-sectional design and 2) changes in the investment asset ratio are most strongly associated with changes in financial satisfaction over time.
Keywords: financial planning; financial therapy